1992
DOI: 10.1016/0014-5793(92)80942-a
|View full text |Cite
|
Sign up to set email alerts
|

CDP‐diacylglycerol synthesis in rat liver mitochondria

Abstract: CDP-diacylglycerol tbr polyglycemphosphatid¢ biogenesis can be synthesized within rat liver mitochondria, This membrane-associated enzym¢ was predominantly lo,zated in the inner mitochondrial membrane. GTP had a significant effect in activating the microson~al CDP.diacylglycerol synthase, especially if the microsomes were preineubated with GTP in the presence of phosphatidic acid. This stlmulatory effect of GTP on the microsomal enzyme was not detected in the mitochondrial fractions, The enzymes could be solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…In rat liver, the majority of CDS activity is found in the microsomal fraction, with some in the mitochondria and nuclei (32). The product of CDS activity (CDP-DAG) can be used to synthesize phosphatidylglycerol as well as PtdIns, and in inositol auxotrophs deprived of inositol there is an increase in phosphatidylglycerol that accompanies the decrease in PtdIns synthesis (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat liver, the majority of CDS activity is found in the microsomal fraction, with some in the mitochondria and nuclei (32). The product of CDS activity (CDP-DAG) can be used to synthesize phosphatidylglycerol as well as PtdIns, and in inositol auxotrophs deprived of inositol there is an increase in phosphatidylglycerol that accompanies the decrease in PtdIns synthesis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Lower panel: Cells were replicately plated in 12-well plastic dishes and allowed to grow for 48 h. The medium was then changed to either serum-free, phosphate-free F-12 medium containing 25 mM HEPES and 50 mCi/ml [ 32 P]orthophosphate for the labeling of PtdIns and PtdCho or serum-free minimal essential medium containing 25 mM HEPES and either 20 mCi/ml radiolabeled arachidonic acid (AA) or 20 mCi/ml radiolabeled oleic acid (OA) plus or minus 50 mM triacsin C (Tc). After another 2 h incubation, lipids were extracted as described in the text and separated by thin-layer chromatography to yield either [ 32 Values shown represent means 6 SD of three separate determinations. Statistical significance for differences seen with triacsin C is as follows: PtdIns, P , 0.0005; PtdCho, no statistical difference; arachidonic acid, P , 0.0025; oleic acid, not determined.…”
Section: Effect Of Pkc Inhibition On the Actions Of Tpamentioning
confidence: 99%
“…The average increase in Cds-specific activity was 7.6-fold. The stimulation of Cds activity by GTP was previously proposed to distinguish the microsomal form of the enzyme, which is activated by GTP, from the mitochondrial form (17,40,41). GTP modulation of Cds activity reported by these investigators was potentially an exciting finding at the time since it suggested the possibility of G protein regulation of the enzyme.…”
Section: Isolation and Structure Of The Cds1 And Pis1 Cdnas-thementioning
confidence: 93%
“…These membrane domains have biochemical properties consistent with the phospholipid-rich, nonraft, ER membrane domains predicted by Shaikh and Edidin ( 35 ). 32 P]CDP-DAG ( 40 ). Fifty microliter samples from each gradient fraction were mixed with an equal volume of assay buffer composed of 20 mM Tris-HCl pH 7.4, 40 mM MgCl 2 , 2 mM EGTA, and 20 Ci/ml [ ␣ 32 P]CTP.…”
Section: Subcellular Fractionation Of A431 Cellsmentioning
confidence: 99%
“…Caveolae were immunoisolated as described previously ( 40 ). For the isolation of calnexin-containing membranes, samples were precleared with 20 µl Protein G Sepharose beads for 1 h at 4°C.…”
Section: Immunoprecipitation Of Caveolae and Calnexin-rich Domainsmentioning
confidence: 99%